A Comparative Study of Quantum Management, Human Resource Productivity and Organizational Empathy in Higher Education (Case Study: Lorestan Universities and Lorestan University of Medical Sciences) - maryam nazarzadeh; Iraj nikpay; abas madandar arani (Institute of Management fekrenoandish, 2021)
Extended AbstractAbstractGiven the role of it in the production of science and knowledge, the higher education is expected to be a pioneer in the application of up-to-date and efficient knowledge. In this regard, the subject of attention to new management methods and the subject of communication in new organizations in order to increase employee productivity is the aim of this study. In the present study, three management concepts compatible with new universities; quantum management, human resource productivity and organizational empathy have been investigated and it is intended to compare the amount of these three variables in Lorestan Universities and Lorestan Medical Science Universities. The present study is applicable in terms of purpose and has been conducted in terms of data collection method with library studies and a prefabricated questionnaire. The statistical population in this study is the staff of Lorestan Universities and Lorestan University of Medical Sciences in 1396 with 863 people, among which 265 people selected by means of the relative classifying sampling via the Krejcie & morgan table as sample, were determined relatively in each class. To compare the variables in the two universities, the data related to the research hypotheses were analyzed using the analysis of variance test. According to data analysis, there is a difference between quantum management and human resource productivity in Lorestan universities and Lorestan University of Medical Sciences, but there is no difference between the levels of organizational empathy in these two universities.IntroductionRapid and continuous changes in the world, the increasing growth of knowledge and information production has led to the need to change organizations from a state of stability and predictability to coordination with the uncertainty in all world situations, including the management of organizations. The ability of change is one of the most vital capabilities of an organization on which the survival and development of the organization depends (Vaezi, Adnan Raad, & Shahmohammadi., 2015). Quantum management increases the level of empowerment of employees and at the same time provides the ground for consultation and synergy by employees and managers (mirkamali & hajkhozeymh, 2020). Today, the importance of empathy in new organizations is clear to everyone. Organizations as a social phenomenon include a number of people who have the ability to cooperate and create different relationships to achieve a common goal and therefore have a high need for empathy in their organization (Amirkabiri, 2002). Empathy is an incentive force for social behaviors and behaviors that lead to group cohesion (Jolliffe & Farrington, 2006; Reef, et al., 2010). Empathy is one of the effective factors on the development of human relations in the organization and consequently leads to psychological improvement in the organization (Shahrasebi, Mooghali, Ahmadi, & Amirkhani., 2019). Given that the existence of organizational empathy has positive effects on the development of organizations and consequently society (Mohammad Shafi'I,., Haghshenas, & Afrough (2015) and also in interpersonal practices, empathy is a factor of success; The leaders, with appropriate methods, can penetrate the beliefs and values ​​of their employees; and cause the dynamism, effectiveness and increasing success of the organization, because there are always shortcomings and weaknesses in the design of organizations. Management and leadership are strong and reassuring factors in creating coordination between members, activities and also leads them in creating their empathy (Pirooz, khedmati, & Beheshtinejad, 2002). Growth and development of organizations, especially universities,  will not be possible without considering the basic element of manpower, because among the factors of production, the manpower factor, unlike other organizational resources, is known as the consciousness and coordinator of other factors. The human source is the most important investment in each organization, and Index of superiority of an organization over other organizations that determines how it operates, performance and ultimately the efficiency of the organization (mardani, shahr, babak & khaki, 2019). Employment of motivated, capable and productive human resources, in addition to providing quality services, can use other resources within the organization in a proper and desirable manner and achieve a variety of productivity aspects And ultimately make the organization productive (Baradaran & Valijani, 2016). Since one of the main goals of higher education is to strive for quality in the set of activities effective in better educational, research and executive performances, The present study seeks to answer the question; whether there is a difference between quantum management, organizational empathy and human resource productivity in Lorestan University and Lorestan University of Medical Sciences?Case study In this study, all employees of Lorestan University and Lorestan University of Medical Sciences, including full-time and part-time employees, contract and formal and pact forces have been working in these universities; has been reviewed as a case study.Theoretical framework Manpower productivity is the maximum appropriate use of manpower in order to achieve the goals of the organization with the minimum time and cost (Azadi, 2014).Quantum management is a fully operational skill for managers, which fits with the characteristics of organizations in the last century. This metaphor for managers' behaviors is derived from quantum theory, which is derived from the field of physics (Golshan, 2003).The existence of a sense of empathy among the members of an organization is called organizational empathy. This empathy must be reflected in the interpersonal relationships between employees, between managers and employees, and between managers. Empathy is one of the factors of internal cohesion of the organization (Davis, 2009).Mirkamali and Haj Khuzimeh (2020) in a study entitled "The relationship between managers 'quantum management skills and staff readiness for organizational change" which was conducted on employees of the University of Tehran showed that there is a positive and significant relationship between managers' quantum management skills and staff readiness for organizational change (mirkamali & hajkhozeymh, 2020).Shahabi Nasab et al. (2021), in their study "The effect of quantum management skills on the formation of innovative work behavior based on the mediating role of psychological empowerment and knowledge management" showed that quantum management skills has a positive and significant effect on innovative work behaviors, knowledge management and psychological empowerment of employees (Shahabi Nasab, Bahrami, Pirzad & Hojjatdoost.2021).MethodologyThe present study is applied in terms of purpose and descriptive-survey in terms of data collection method. The statistical population of this study is all employees of Lorestan University and Lorestan University of Medical Sciences, who have been working in these universities in the academic year 2017-2018. The statistical population of this study is 843 people, which according to Krejcie and Morgan (1970) table, 265 people have been selected as a sample. Using the relative class sampling method, a sample of 126 people from Lorestan University and 139 people from Lorestan University of Medical Sciences were selected. Data collection tool consists of three prefabricated questionnaires.Discussion and ResultsAnalysis of variance was used to analyze the data related to the hypotheses. Since the significance level (0.00) of quantum management in Lorestan Universities and Lorestan University of Medical Sciences is less than the error level of 0.05; therefore this hypothesis is confirmed and there is a difference between the amount of quantum management in Lorestan Universities and Lorestan University of Medical Sciences. Since the significance level (0.09) of organizational empathy between Lorestan Universities and Lorestan University of Medical Sciences is greater than the Error level of 0.05; therefore, this hypothesis is not confirmed and there is no difference between the level of organizational empathy in Lorestan universities and Lorestan University of Medical Sciences.